The university's entrepreneurship training by SME Bank in improving Bumiputera business performance / Fazura Nur Zaher - Zaher, Fazura Nur (Faculty of Business and Management, 2007)
It is well established that the university institutional environment encourages the acquisition and dissemination of new knowledge among university community members. However, what is less well understood is how the university institutional environment encourages entrepreneurial (opportunity discovery, evaluation, and exploiting) behavior. The development of entrepreneurship, as both concept and activity, has been growing in importance in Malaysia. The perceived importance of entrepreneurship to the growth of Malaysia's economy is evidenced by the sheer amount and variety of supporting mechanisms and policies that exist for entrepreneurs, including funding, physical infrastructure and business advisory services. This paper reports on one of the outcomes of a broad ranging research project, funded by the SME Bank, aimed at investigating the potential for the assessment of entrepreneurial ability in undergraduate students. SME Bank proposes to the government to have this entrepreneurship training to be done in every university for early expose for students to involve in entrepreneurship. In getting the data and information needed, the primary data have obtained from the survey method. It was more to quantitative research, where survey instrument in which questionnaires, have been used in this study. It involved a structured questionnaire given to the respondents to elicit specific information. The sample for this study was the students of UiTM Malacca and UNIKL (MIIT). One hundred (100) sets of questionnaire have been distributed personally to one hundred respondents but only 65 are usable. Overall, this study has come up with a new research model according to the sources of previous study.